Salesforce platform app builder certification : a practical study guide - Gupta, Rakesh (Salesforce consultant) (Apress L.P., 2020)
New or intermediate developers will want to use this hands-on guide to prepare for the Salesforce Certified Platform App Builder credential, awarded for designing, building, and implementing applications using the declarative customization capabilities of the Salesforce Platform. This is the first book available covering this content, and Salesforce training is very costly. This book is filled with real-world examples and hands-on exercises, enabling you to prepare for the certification exam in a short span of time. Multiple-choice study questions and exercises are included to help you apply what you learn in each chapter. Author Rakesh Gupta explains Salesforce Platform fundamentals, including knowledge about the limitations of the declarative platform and when to use programmatic development versus the AppExchange. Data management and data analytics are covered. And you will learn how to set up organization-wide features that affect the look and feel of your application. Sandbox design patterns and process automation tools available in Salesforce are discussed and you will know when to use them. You will become familiar with a wide array of topics, including designing a mobile app and reporting in Salesforce. You will: Know when to use declarative development versus programmatic development versus the AppExchange Understand the Salesforce data model, field type (when to use which fields), and how and when to use an external object in Salesforce Be familiar with security and settings in Salesforce See how easily users can migrate to the Lightning experience from the classic platform Implement business process automation using declarative features Apply the automation process in Salesforce Utilize Process Builder and manage its power to automate business processes Use sandboxes and deployment tools.